La casación penal ecuatoriana - Jaime Flor Rubianes (Universidad Hemisferios, 2008)
This paper presents in a didactic way the thesis, the application procedure and the consequences of a criminal appeal in Ecuador. Develops carefully whether and in what areas it should bring this action. It also includes the historical evolution of the appeal in our penal system.